Performing British Identity: Arthur on Screen - Varandas, Angélica (2014)
Arthur is by far the most paradigmatic British hero. Appearing for the first time in the literary, as well as in the historical and political context of medieval Wales, as a Celtic war hero opposing the Saxon invaders, he soon crossed the borders of the Welsh territory to become the king of an entire nation. With the contribution of Geoffrey of Monmouth and subsequently of French and English medieval writers, Arthur not only turned into a symbol of kingship but mainly into the face of British territory and identity, embodying the fate and hopes of the British people. As a messianic hero, he is par excellence the protector of the land, a role fulfilled in the past that will be reenacted in a possible future. From the Middle Ages onwards, the figure of Arthur has lured writers, painters, and artists in general. It is no wonder then that screen-writers and film directors also felt attracted to this potent hero and decided to celebrate his deeds through motion pictures. Is it thus our intention in this paper to reflect about Arthur and his presence on screen, taking two main films into consideration: Excalibur by John Boorman (1981) and King Arthur by Antoine Fuqua (2004).